Put an End to Manual Data Entry: How Small Businesses Can Adapt The Changes and Transform? - Zetty Ain, Kamaruzzaman; Zaini, Muhamad Zuhaili; Noraina Mazuin, Sapuan (Penerbit UTHM, 2021)
In today’s fast-paced digital era, data and information is the most valuable asset to businesses. The phrase “data is the new oil” was originally coined by Clive Humby, a British mathematician, and data science entrepreneur, in 2006. Later in year 2017, The Economist published an article entitled “The world's most valuable resource is no longer oil, but data”. Since then, this metaphor has commonly been used worldwide. This metaphor has clearly grown in popularity over the last decade, but is it a sound way of looking at business data? Is there a new approach or better way to think and conceptualize business data that will help organizations better grasp the function it plays in the 21st-century business world? How should businesses utilize their data as a valuable resource?